Prevención de la infracción penal de adolescentes - Arandia-Zambrano, Juan Carlos; Díaz-Basurto, Ingrid Joselyne; García-Pilligua, Nury Magdalena (IUSTITIA SOCIALIS, 2021)
Prevención de la infracción penal de adolescentes